Weeds. Season five - Kohan, Jenji, 1969-; Parker, Mary-Louise; Perkins, Elizabeth, 1960-; Parrish, Hunter, 1987-; Gould, Alexander, 1994-; Nealon, Kevin, 1953-; Kirk, Justin; Ellis, Scott; Morrow, Victoria; Pressman, Michael; Benabib, Roberto; Salsberg, Matthew; et al. (Santa Monica, Calif. : Lionsgate, 2010)
Nancy is pregnant with the child of a powerful politician turned dangerous drug lord, or is she? Doug and Silas are trying to branch out on their own, Andy is looking to score, and Celia attempts to turn the tables on her kidnappers. With enemies out to smoke the Queen of Green, Nancy's sure to find a whole new crop of trouble
Disc 3. Episode 10: Perro insano / written by David Holstein ; directed by Scott Ellis -- Episode 11: Ducks and tigers / written by Stephen Falk ; directed by Matt Shakman -- Episode 12: Glue / written by Ron Fitzgerald ; directed by Michael Pressman -- Episode 13: All about my mom / written by Jenji Kohan ; directed by Scott Ellis
Originally broadcast on Showtime as individual episodes during the 2009 season
Title from container
Contains all 13 episodes from the fifth season
Special features: Cast and crew commentaries; bloopers; "History of weed" featurette; "Yes we cannabis" featurette; "Crazy love: a guide to the dysfunctional relationships of Weeds" featurette; "Little titles by Jenji Kohan" featurette; "University of Andy" featurette; "Really backstage with Kevin Nealon" featurette
Production credits vary by episode
Mary Louise Parker, Elizabeth Perkins, Hunter Parrish, Alexander Gould, Kevin Nealon, Justin Kirk
Keywords: Marijuana industry -- United States -- Drama; Women drug dealers -- United States -- Drama; Drug traffic -- United States -- Drama; Criminal behavior -- United States -- Drama; Families -- United States -- Drama; Widows -- Drama; Mothers -- Drama; Kidnapping -- United States -- Drama; DVD-Video discs; Video recordings; Drama